Marriages are Made in Kitchens: The European Marriage Pattern and Life-Cycle Servanthood in Eighteenth-Century Amsterdam. Issue 2 (3rd April 2017) - Boter, Corinne
ABSTRACT: Due to methodological difficulties of historical research on women's labor, little is known of women's contribution to household incomes in preindustrial economies. This article is the first to use domestic servants' wages, as documented in account books from the period 1752–1805, to estimate the capital that women could accumulate during their years of service before marriage. As such, it offers a new perspective on women's contribution to household resources. Results show that servants working for the most well-off households in eighteenth-century Amsterdam could save a marriage budget that was between one-third and half of the capital that an unskilled man could save in the same amount of time. Furthermore, servants' wages would in theory have been sufficient to support a family of four at the subsistence level, illustrating that women's wages and potential savings cannot be ignored.